Primary school Teachers’ additive problem-posing of word-problem in Mexico (Encuentros, 2023)
In this article, the challenging additive word problems created by a group of Primary School teachers in Mexico were analyzed. Using a qualitative methodology, data were collected in a workshop where teachers created their problems and were examined through content analysis based on the classification of additive problems according to their semantic structure. The findings show that most teachers create problems with change structures in the unknown in the final quantity and combination problems with the unknown quantity in the whole. The teachers proposed a few comparison and matching problems that are the most challenging, but problems with compound semantic structures were evident. It is concluded that it is important to continue researching additive comparison and equalization problems or problems (one and several stages) that require the connection between different semantic structures for their resolution, in order to train mathematically competent students from an early age.
Keywords: Problem-posing, additive word problems, semantic structure, Primary school teachers.